Narrativas (auto)biográficas, resistência e empoderamento: uma proposta para a formação de professores suleada pela práxis decolonial a partir da afroperspectiva - Santos, Tereza de Jesus dos (2024)
The present study was developed in the context of the Postgraduate Program in Technological Education at the Federal Institute of Amazonas, Manaus -Centro campus, in the research line I Processes for Effectiveness in Teacher Training and Pedagogical Work in Technological Teaching Contexts. The research emerges from the urgency of recognizing and valuing the quality of ethnic-racial diversity that is included in our society. For this purpose, our general objective proposes to discuss teaching experiences and propose teacher training anchored in a pluriversal, anti racist and decolonial approach for teachers working in Basic Education. From this, we seek to question the theme in question, in which refers to teacher practices, pointing out a break with the legacy of the European colonial civilization process that still structures Brazilian society, thus showing a training perspective for ethnic-racial diversity. In the development of our investigative proposal, we formed a teaching group from different areas of knowledge as well as an activist in the black movement. To carry out the research, as well as the elaboration of our educational product proposal, the biographical project studio, we suggest from the perspective of qualitative research, anchored in (auto) biographical narratives with theoretical sport, among other authors, Delory-Momberger (2006- 2012), Freire (2009, 2016, 2017), Gomes (2008, 2017, 2019, 2023), Goodson (2019), Josso (2006), Minayo (2017), Rufino (2019, 2021, 2023), Souza (2008 ). , 2011, 2015, 2016), Nóvoa (2009, 2023). Because of this, our theoretical support contributed to a dialogue/reflection in the anti-racist struggle through the possibilities of constructing proposals for teachers to reframe their practices, recognizing and valuing the ethnic-racial diversity that exists in our society and thus, breaking with the structure that carries the still predominant model of education, the legacy of the colonial project, which was based on the destruction, silencing and erasure of non-white beings. Our methodological contribution followed the qualitative approach in the following methods: (auto)biographical narratives and pedagogical letters. In the first moment of the investigation In the field, the work with pedagogical letters was developed, where teachers exchanged letters narrating their trajectories. our work. In view of this, we believe that our research contributed to the participating teachers and has great potential to contribute to many others who later come to participate in the studio effectively from a perspective of rupture and new meaning of their practices in favor of anti-racist education, decolonial and pluriversal in the construction of an equitable, supportive, democratic and racism-free society, welcoming other knowledge, other voices and other ways of being in the world.